Operational Risk Assessment of an English Academy in Yogyakarta - Ismawati, Anastasia Filiana (Jurnal Entrepreneur dan Entrepreneurship, 2020)
This research was conducted for the risk assessment on the operational activities in order to assist PT. XYZ in managing the operational activities which leads to the goals of the firm. The use of Enterprise Risk Management (ERM) can help the organization to manage the risks holistically using the intergrated methods. This research focused on the risk assessment in PT. XYZ, especially for its operating, and provided a strategy of improvement from the existing risks. The methodology used in this research is a case study with triangulation of sources as the tool to conduct the data analysis. The informants of this research are the Operational Manager of PT. XYZ and five teachers. The data was obtained by conducting interviews and there were six operational risks found which would be best to respond and to manage as soon as possible for minimizing the risks. The result of this research is to hope that PT. XYZ shall be able to manage the risks by using the ERM methodology in order to have the business in the long run and to be successfully competing in the market.